Legal Liabilities of Celebrities in False Advertising Through Endorsement in Indonesian Civil Law Perspective - Jennifer, Jennifer; Paramitha, Chintya Lie; Shahan, Akbar Helmie Nur; Gunadi, Ariawan (Journal of Health Education Law Information and Humanities, 2025)
In the contemporary marketing landscape, celebrity endorsements have emerged as a powerful strategy for brand engagement. However, the proliferation of false advertising through these endorsements necessitates a critical examination of legal frameworks and accountability mechanisms. This research investigates the legal liabilities of celebrities in false advertising, analyzing the intricate legal frameworks, regulatory mechanisms, and consumer protection principles within Indonesian civil law. By exploring the intersection of contractual obligations, consumer rights, and ethical responsibilities, the study aims to provide insights into the legal accountability of celebrities in marketing practices. The proliferation of celebrity endorsements in contemporary marketing has raised critical questions about legal accountability and consumer protection. This research investigates the legal liabilities of celebrities in false advertising, providing a comprehensive analysis of the intricate legal frameworks, regulatory mechanisms, and consumer protection principles within Indonesian civil law. By exploring the intersection of contractual obligations, consumer rights, and ethical responsibilities, the study offers insights into the legal accountability of celebrities in marketing practices.